Improving the Safety of Hospital Complexes in Modern Conditions - Ivanovich, Vaulin Vladimir; Aleksandrovich, Singeev Sergey (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Any medical facility is an object of increased fire danger and this danger is combinedwith the constant presence of a large number of people. The article presents the results of a study ofensuring fire safety in medical and preventive institutions (LPI) based on the example of the centralcity hospital in Russian Federation. Objective: This research was aimed at improving the fire safetyof hospital complexes and hospitals in modern conditions. Methods: The study used the methods ofsystem analysis of scientific research and statistical data on ensuring fire safety, methods of structuralanalysis of the practice of ensuring fire safety of hospital complexes, mathematical methods forcalculating the evacuation of people from a building and the spread of a fire in a building, methodsfor calculating the economic efficiency of means of support fire safety. Results: Based on the analysisof fire statistics in healthcare facilities in Russia, it is concluded that it is advisable to improve thefire safety of hospitals and hospital complexes in modern conditions. The point of view is expressedthat along with the fact that fire safety in hospitals is observed, the analysis indicates the existingproblems in the practice of implementation. Conclusion: In order to increase the level of fire safety,it is possible to introduce: a modern fire alarm system; video of control systems and monitoring ofsafety of objects on the territory of the medical facility; installation of automatic fire extinguishingsystems in fire-hazardous premises; installation of additional emergency lighting and reflectorsindicating the direction of evacuation in case of fire and smoke; carrying out organizational andpractical measures to ensure the safety of patients in a medical institution in an emergency situation(ES), namely, it is proposed to develop a memo of actions for patients in the hospital complex oninpatient treatment in case of an emergency with a list in the instruction log; provision of medicalfacilities with individual rescue equipment and provision of hospitals and hospital complexes withhigh-rise buildings with modern evacuation means. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 335-340